2013
DOI: 10.1021/bc4003844
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Lipophilicity of Peptide Drugs: Replacement of the Backbone N-Methyl Group of Cilengitide by N-Oligoethylene Glycol (N-OEG) Chains

Abstract: Cilengitide is an RGD-peptide of sequence cyclo[RGDfNMeV] that was was developed as a highly active and selective ligand for the αvβ3 and αvβ5 integrin receptors. We describe the synthesis of three analogues of this peptide in which the N-Me group has been replaced by N-oligoethylene glycol (N-OEG) chains of increasing size: namely N-OEG2, N-OEG11, and N-OEG23, which are respectively composed of 2, 11, and 23 ethylene oxide monomer units. The different N-OEG cyclopeptides and the original peptide were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Similar findings were reported for cilengitide. For this N ‐methylated cyclopeptide, replacement of its backbone N ‐Me group by a short N ‐oligoethylene glycol ( N ‐OEG) chain provided a more lipophilic analog with a similar biological activity, and lipophilicity was enhanced upon increasing the length of the OEG chain . In another study, they synthesized an N ‐(4‐azidobutylated) analog of cilengitide, and conjugated it with a polyethylene glycol (PEG) chain through several chemical transformations.…”
Section: Classes Of Backbone N‐substituted Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported for cilengitide. For this N ‐methylated cyclopeptide, replacement of its backbone N ‐Me group by a short N ‐oligoethylene glycol ( N ‐OEG) chain provided a more lipophilic analog with a similar biological activity, and lipophilicity was enhanced upon increasing the length of the OEG chain . In another study, they synthesized an N ‐(4‐azidobutylated) analog of cilengitide, and conjugated it with a polyethylene glycol (PEG) chain through several chemical transformations.…”
Section: Classes Of Backbone N‐substituted Peptidesmentioning
confidence: 99%
“…In several reports on the acylation of N ‐substituted peptides in solid phase, bis(trichloromethyl)carbonate (BTC) was found to be the most efficient activating reagent . This activating reagent, which is considered to convert amino acids into their corresponding acid chlorides, was introduced by Gilon et al They demonstrated that a wide range of Fmoc‐amino acids can be efficiently coupled to various functionalized N‐ alkyl peptides using BTC (Table , entry v), and reported the use of BTC in the SPPS of several N ‐backbone cyclic peptides .…”
Section: Synthetic Strategies For Backbone N‐substituted Peptidesmentioning
confidence: 99%
“…26 More recently, Albericio and coworkers have reported the synthesis of N-oligoethylene glycol (N-OEG) substituted cyclic peptides: sansalvamide A with 3 repeat units of N-OEG 27 and cilengitide with different repeat units of N-OEG such as 2, 11 and 23. 28 The synthesis of cilengitide with N-OEG 2 and sansalvamide A with N-OEG 3 by solid-phase peptide synthesis in multiple steps was reported; however, peptides with longer N-OEG substitutions were very complicated to synthesize and were reported to require extensive purification steps. 28 In the current work, we are introducing anionic ring-opening polymerization (AROP) as a novel technique to create peptides with N-polyether derivatives in a one-step reaction without sophisticated purification steps.…”
Section: Introductionmentioning
confidence: 99%
“…28 The synthesis of cilengitide with N-OEG 2 and sansalvamide A with N-OEG 3 by solid-phase peptide synthesis in multiple steps was reported; however, peptides with longer N-OEG substitutions were very complicated to synthesize and were reported to require extensive purification steps. 28 In the current work, we are introducing anionic ring-opening polymerization (AROP) as a novel technique to create peptides with N-polyether derivatives in a one-step reaction without sophisticated purification steps. AROP is an effective method which is frequently used to synthesize various functional polymers readily applicable in the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…Even though high biodegradability, low bioavailability and low cellular uptake may be some of the limitations of peptide drugs, they can benefit from novel synthetic strategies for enhancing their drug-like properties (Pandey et al 2009;Vlieghe et al 2010). Currently, modifications that a prospective peptide drug candidate can undergo to enhance their efficacy include peptide stapling (Verdine and Hilinski 2012), backbone replacement (Fernández-Llamazares et al 2014), non-natural amino acid incorporation, pseudo peptide bonds, cyclization (Gentilucci et al 2010), conjugation (Gauthier and Klok 2008;Ahrens et al 2012) and so on.…”
Section: Introductionmentioning
confidence: 99%